2019
DOI: 10.1016/j.molcel.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

An Oxygen-Dependent Interaction between FBXL5 and the CIA-Targeting Complex Regulates Iron Homeostasis

Abstract: Highlightsd The CIA-targeting complex interacts with, but is not a substrate of, FBXL5d The CTBD domain of FBXL5 is critical for interaction with the CIA-targeting complex d The CIA-targeting complex stimulates FBXL5-mediated polyubiquitination of IRPs d O 2 levels regulate the FBXL5-CIA-targeting complex interaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…Recent studies have revealed an interaction between FBXL5 and the cytosolic iron-sulfur cluster assembly (CIA)-targeting complex, which is sensitive to oxygen and promotes IRP2 ubiquitination (Mayank et al, 2019;Tan et al, 2013). Although it is tempting to speculate that the [2Fe2S] cluster is loaded onto FBXL5 by the CIA-targeting complex, their functional relationship calls for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed an interaction between FBXL5 and the cytosolic iron-sulfur cluster assembly (CIA)-targeting complex, which is sensitive to oxygen and promotes IRP2 ubiquitination (Mayank et al, 2019;Tan et al, 2013). Although it is tempting to speculate that the [2Fe2S] cluster is loaded onto FBXL5 by the CIA-targeting complex, their functional relationship calls for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…FBXL5 stability is also affected by oxygen levels. Under low oxygen hypoxic conditions, an allosteric-induced stabilizing interaction between FBXL5 and the cytoplasmic Fe-S cluster biogenesis complex CIA is disrupted leading to enhanced FBXL5 instability and increased IRP2 levels, highlighting again the extensive crosstalk between iron regulation and other important processes such as oxygen sensing (Mayank et al, 2019). Indeed, IRP2 deficiency switches cellular metabolic pathways from oxidative phosphorylation (OXPHOS) to aerobic glycolysis (Li et al, 2019) through induction of hypoxia-inducible factors (HIF)-1α and−2α which enhances glycolytic pathway proteins and, at the same time, blocks mitochondrial Fe-S cluster biogenesis and OXPHOS.…”
Section: Iron Cycle—iron Export From the Cellmentioning
confidence: 99%
“…Loss of IRP2 enables translation of mRNAs that contain IREs at the 5 0 -UTR and leads to destabilization and nucleolytic degradation of TFR1 mRNA (8). target proteins, raising the possibility that FBXL5 receives its cluster from the CIA complex; however, abrogation of FBXL5-CIA interaction only partially compromised IRP2 binding to FBXL5 (Mayank et al, 2019), consistent with the possibility that FBXL5 may directly acquire its cluster from the initial cytosolic biogenesis machinery that is actively expressed in mammalian cells (Kim et al, 2018).…”
mentioning
confidence: 90%
“…Another interesting question relates to how FBXL5 acquires its cluster in the cytosol. FBXL5 was previously found to interact with the Cytoplasmic Fe-S Assembly (CIA) targeting complex (Mayank et al, 2019), a protein complex that donates fully synthesized ISCs to Under iron deficiency conditions, the N-terminal hemerythrin (Hr) domain of FBXL5, which contains a di-iron center, cannot bind iron and undergoes conformational changes that destabilize the entire protein and cause its ubiquitination and degradation (1), leading to stabilization of IRP2 (2). IRP2 binding to the Iron Responsive Elements (IREs) at the 5 0 untranslated regions (UTRs) of the messenger RNAs (mRNAs) of ferritin H and L (FTH and FTL), the erythroid-specific aminolevulinic acid synthase (ALAS2), HIF2a, and mitochondrial aconitase (ACO2) represses their translation, whereas binding of IRP2 to the 3 0 -UTR of the mRNA of transferrin receptor (TFR1) stabilizes the transcript and enhances its translation (3).…”
mentioning
confidence: 99%